The Mediating Role of Good Corporate Governance on the Relation between Intellectual Capital and Financial Performance - Nurul Aini; Akhmad Zainuddin (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to examine the role of good corporate governance (board of directors and board of commissioners) in mediating the bond between intellectual capital and financial performance. Design/methodology/approach: This study obtains data from 264 manufacturing companies listed on the Indonesia Stock Exchange in the 2015 – 2020 period. This study employs the Warp PLS 7.0 program. The tested research model is the multiple mediator model, with more than one mediating variables, so it requires multiple mediation analysis. Findings: The results reveal that intellectual capital has no effect on financial performance. Intellectual capital has a significant negative effect on the board of directors and board of commissioners, while the board of directors and board of commissioners have a significant positive effect on financial performance. Practical implications: Intellectual capital affects financial performance through the board of directors and board of commissioners’ as the mediating variables supported by the category of competitive mediation (inconsistent mediation). This competitive mediation provides support for the mediating effect hypothesis. Paper type: Research paper